Oxaliplatin-Induced Tonic-Clonic Seizures - Rahal, Ahmad K. (Case Rep Oncol Med, 2015)
Oxaliplatin is a common chemotherapy drug used for colon and gastric cancers. Common side effects are peripheral neuropathy, hematological toxicity, and allergic reactions. A rare side effect is seizures which are usually associated with posterior reversible leukoencephalopathy syndrome (PRES). A 50-year-old male patient presented with severe abdominal pain. CT scan of the abdomen showed acute appendicitis. Appendectomy was done and pathology showed mixed adenoneuroendocrine carcinoma. Adjuvant chemotherapy was started with Folinic acid, Fluorouracil, and Oxaliplatin (FOLFOX). During the third cycle of FOLFOX, the patient developed tonic-clonic seizures. Laboratory workup was within normal limits. EEG and MRI of the brain showed no acute abnormality. The patient was rechallenged with FOLFOX but he had tonic-clonic seizures for the second time. His chemotherapy regimen was switched to Folinic acid, Fluorouracil, and Irinotecan (FOLFIRI). After 5 cycles of FOLFIRI, the patient did not develop any seizures, making Oxaliplatin the most likely culprit for his seizures. Oxaliplatin-induced seizures rarely occur in the absence of PRES. One case report has been described in the literature. We present a rare case of tonic-clonic seizures in a patient receiving Oxaliplatin in the absence of PRES.